Characteristics of The Local Wisdom from South Borneo In Ecological Aspect - Nida Humaida; Virgina Maria Louisa; Nana Citrawati Lestari (ESE International Journal (Environmental Science and Engineering), 2018)
Local wisdom in some local communities in Indonesia is used as the basis to manage their environment. Their traditional judgments even in line with sustainable development goals rather than current modern policy. In this paper, we focused on a literature study about the ecological aspect of the local wisdom of South Borneo society, such as their agriculture system, irrigation system, river society, traditional house, and philosophical values. Despite slower productivity compared with using modern technology, we conclude South Borneo’s local wisdom in ecological aspect showed harmonious relationship between humans and their natural environment. The advancement of modern technology, consumerism, and socio-economic competition in accessing natural resources becomes a big challenge for policymakers to achieve sustainable development.